A Review on Nozzle Wear in Abrasive Water Jet Machining Application - Syazwani, H.; Mebrahitom, A.; Azmir, Azhari (IOP Publishing, 2016)
This paper discusses a review on nozzle wear in abrasive water jet machining application. Wear of the nozzle becomes a major problem since it may affect the water jet machining performance. Design, materials, and life of the nozzle give significance effect to the nozzle wear. There are various parameters that may influence the wear rate of the nozzle such as nozzle length, nozzle inlet angle, nozzle diameter, orifice diameter, abrasive flow rate and water pressure. The wear rate of the nozzle can be minimized by controlling these parameters. The mechanism of wear in the nozzle is similar to other traditional machining processes which uses a cutting tool. The high pressure of the water and hard abrasive particles may erode the nozzle wall. A new nozzle using a tungsten carbide-based material has been developed to reduce the wear rate and improve the nozzle life. Apart from that, prevention of the nozzle wear has been achieved using porous lubricated nozzle. This paper presents a comprehensive review about the wear of abrasive water jet nozzle.